Dual-Energy CT to Diagnose Occult Femoral Neck Fracture in MRI-Contraindicated Patient: A Case Report. Issue 4 (14th October 2021) - Rogers, Nathan B.; Karam, Wade N.; Kumaravel, Manickam; Warner, Stephen J.; Gary, Joshua L.
Abstract : Case: A 79-year-old woman presented after a ground level fall with the inability to bear weight on her right hip. Radiographs and computed tomography (CT) imaging were negative for a femoral neck fracture. Her medical comorbidities precluded magnetic resonance imaging (MRI), so dual-energy CT with focused evaluation for bone edema was performed, identifying a femoral neck fracture that was stabilized surgically. Conclusion: Dual-energy CT with processing for edema can successfully identify nondisplaced femoral neck fractures in MRI-contraindicated patients. This imaging modality could be useful for diagnosing femoral neck stress fractures and ipsilateral femoral neck fractures in patients sustaining high-energy femoral shaft fractures.